1986
DOI: 10.1002/1098-108x(198607)5:5<837::aid-eat2260050505>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in restricter-type anorexia nervosa: A study of six women

Abstract: Six restricter type women with anorexia nervosa were interviewed regarding their pregnancies and four of the women were interviewed again three to four months following the birth of their children. Although these women were able to nutritionally sustain their fetuses during pregnancy, and there was a mitigation of their anorectic behaviors during pregnancy, all returned to their pre‐pregnancy anorectic thinking and behaviors following the births. The effects of the pregnancies on various aspects of their lives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
7

Year Published

1989
1989
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 5 publications
(5 reference statements)
2
36
0
7
Order By: Relevance
“…As mulheres com perturbação do comportamento alimentar tendem a amamentar os filhos por períodos de tempo mais curtos que as mulheres sem perturbação (Larsson & Andersson-Ellström, 2003;Namir et al, 1986). Ao mesmo tempo, enquanto alguns autores alegam que a prematuridade, as complicações obstétricas e o baixo peso podem aumentar o risco de desenvolvimento de anorexia nervosa mais tarde, denominado o "ciclo de risco" (Bulik et al, 2005), outros autores consideram que episódios traumáticos no início de vida não parecem aumentar a susceptibilidade para o desenvolvimento de sintomatologia associada a perturbações do comportamento alimentar (Feingold, Sheir-Neiss, Melnychuk, Bachrach, & Paul, 2002).…”
Section: Riscos Associadosunclassified
See 3 more Smart Citations
“…As mulheres com perturbação do comportamento alimentar tendem a amamentar os filhos por períodos de tempo mais curtos que as mulheres sem perturbação (Larsson & Andersson-Ellström, 2003;Namir et al, 1986). Ao mesmo tempo, enquanto alguns autores alegam que a prematuridade, as complicações obstétricas e o baixo peso podem aumentar o risco de desenvolvimento de anorexia nervosa mais tarde, denominado o "ciclo de risco" (Bulik et al, 2005), outros autores consideram que episódios traumáticos no início de vida não parecem aumentar a susceptibilidade para o desenvolvimento de sintomatologia associada a perturbações do comportamento alimentar (Feingold, Sheir-Neiss, Melnychuk, Bachrach, & Paul, 2002).…”
Section: Riscos Associadosunclassified
“…Também Lewis e Grange (1994) verificaram que as mulheres com perturbação do comportamento alimentar mais grave na gravidez foram as mesmas que se separaram ou divorciaram depois, o que levanta a hipótese de que as mulheres com percepção de relações estáveis estavam mais aptas a controlar os sintomas bulímicos durante a gravidez do que as que tendiam a ter problemas interpessoais, resultados que estão de acordo com outros autores (como Lacey & Smith, 1987). Por outro lado, as mulheres podem sentir as relações conjugais como tendo efeitos negativos, nomeadamente no que respeita às suas inseguranças acerca da aparência e aos comentários dos cônjuges quanto às quantidades de comida ingerida (Namir et al, 1986).…”
Section: Riscos Associadosunclassified
See 2 more Smart Citations
“…The results of studies on small numbers of subjects are contradictory, but the best of these (Stewart et al 1987) found that a majority of anorexics experienced a worsening of symptoms while 12 of 13 recovered cases remained well. In a smaller uncontrolled study, 6 anorexics were found to improve their calorie intake during pregnancy (Namir et al 1986). …”
Section: Weight Gain In Pregnancy and Exacerbation Of Eating Disordersmentioning
confidence: 99%